Vericiguat and health status outcomes in heart failure with reduced ejection fraction: insights from the VICTORIA trial. (14th October 2021) - Butler, J; Stebbins, A; Melenovsky, V; Sweitzer, N; Cowie, M.R; Stehlik, J; Ezekowitz, J.A; Hernandez, A.F; Lam, C.S.P; Nkulikiyinka, R; O'Connor, C.M; Pieske, B; et al.
Abstract: Background: In the VICTORIA trial, vericiguat compared with placebo reduced the risk of the primary endpoint of cardiovascular death (CVD) or hospitalization for heart failure (HFH) among 5050 patients with worsening HF with reduced ejection fraction (HFrEF). Purpose: We evaluated whether the efficacy of vericiguat on clinical outcomes varied according to participants' baseline health status, as assessed by the Kansas City Cardiomyopathy Questionnaire (KCCQ)-23, and how vericiguat affected health status post-randomization. Methods: KCCQ-23 was completed at randomization and at 4, 16, and 32 weeks. Patients were grouped based on tertiles of baseline KCCQ total symptom score (TSS; <55.2, 55.2–79.2, and >79.2), clinical summary score (CSS; <52.1, 52.1–76.0, and >76.2) and overall summary score (OSS; <48.5, 48.5–70.8, and >70.8) across tertiles 1–3, respectively. Cox proportional hazard models were performed for the tertiles to evaluate the effects of vericiguat on the primary outcomes. Results: Overall 4741, 4664, and 4470 participants had KCCQ-TSS (median 68.8 [interquartile range 47.9, 85.4]), KCCQ-CSS (65.6 [45.8, 81.8]) and KCCQ-OSS (59.9 [42.0, 77.1]) available at baseline. Vericiguat reduced CVD or HFH risk across baseline KCCQ-TSS (P=0.21), KCCQ-CSS (P=0.13) and KCCQ-OSS (P=0.65) tertiles (Table). The effect of vericiguat on HFH alone was also not modified by baseline KCCQ-TSS, CSS and OSS (all P>0.05) scores. At 4 weeks after randomization, improvement in both vericiguat and placebo arms was seen in KCCQ-TSS (vericiguat 6.3 vs. placebo 6.3; P=0.85), KCCQ-CSS (vericiguat: 5.7 vs. placebo 5.7, P=0.54), and KCCQ-OSS (vericiguat 6.3 vs. placebo 5.7, P=0.36). Similar results were seen at weeks 16 and 32. Conclusion: Vericiguat reduced the risk of the composite outcome of CVD or HFH as well as HFH alone across the range of baseline health status. Addition of vericiguat to best standard of care did not significantly improve health status compared with standard of care alone in HF patients with a recent worsening event. The early improvement in KCCQ seen in both randomized groups underscore the need to assess trajectory of health status changes in the spectrum of patients with HFrEF. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Merck & Co., Inc. and Bayer